(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research dealt with the risks of reinsurance and its impact on the financial performance of the National Insurance Company by focusing on reinsurance in the marine insurance branch. Negative impact on the financial performance of the NICs and the Marine Insurance Branch. The research sample resulted in a main hypothesis that reflects this relationship. Lee in the analysis of financial information reports National Insurance Company of the branch of marine insurance for the period of 2010 until 2017, and the use of (retention) for measuring the re-insurance operations index, and (insurance financial surplus rate) to measure financial performance. For the purpose of obtaining the results, a number of statistical methods were used according to the nature of the collected data. In the light of these results, the researcher reached a number of conclusions concerning the applied side, the most important of which (the results of financial and statistical analysis showed that there is a significant effect of the retention ratio of the maritime insurance branch in the financial surplus, and based on the conclusions reached by the research has been made a set of recommendations To the researched company that is consistent with the reality of the research, the most important (the need to review the company retention policy and to reduce the rate of return to the appropriate extent).